Heritagutopia: a new utopian paradigm - Luca Donner; Francesca Sorcinelli (City, Territory and Architecture, 2024)
Abstract The progress of humanity has always, and sometimes even unconsciously, been confronted with the concept of utopia at the social, economic, political, and urban level. The strength of every utopian vision lies in the disruptive factor inherent in the idea of metamorphosis of the status quo. In the urban context, it represents the pillar on which the vision of modern society and its city are based and understood as potential and progress for mankind. Authors such as Bauman, Bloch, Calvino, More, Mumford, Tafuri, and others, have formed the theoretical framework of the dialectic on which this study is based. As we know, the history of architecture and urban planning provides multiple models of utopia that have alternated over time, such as the ones proposed in the 60 and 70 s by Archigram, Superstudio, Yona Friedman or the Japanese Metabolist movement, just to name a few. Starting from these experiences at the urban scale, and supported by contributions from disciplines such as philosophy, literature, and sociology, this research defines a new model of utopia called “Heritagutopia”. It is a new utopian paradigm, and not dystopian as it will be demonstrated, which is based on the symbiosis between urban historical heritage and abandoned industrial areas or run-down infrastructures. The first one, due to the centripetal economic dynamics, leaves its current location to find exile in the second one, through parasitic urban tactics. It is a migration, or an exile in some ways. However, in both cases this new condition allows the two contexts not to vanish and to regain possession of their lost identity, or rather to regenerate themselves, acquiring a new life. It allows to break into custom with a vision that undermines the state of affairs, subverts its factors, by proposing an alternative vision, sometimes dreamlike, but deliberately provocative as every utopia wants to be.